Minimally Invasive Load-Sharing Implant for Medial Compartment Knee Osteoarthritis. Issue 4 (December 2015) - Madonna, Vincenzo; Zorzi, Claudio; Crawford, Dennis C.; Miller, Larry E.; Block, Jon E.
Abstract : There is a distinct need for minimally invasive surgical options for the treatment of knee osteoarthritis. This manuscript describes a minimally invasive implant that reduces the load carried by the medial compartment of the knee joint during the stance phase of gait. Implantation is achieved without resection of bone, muscle, or ligaments and without violation of the joint capsule. The procedure is completely reversible should the need arise, allowing for simple device removal without comprising future surgical options. The surgical techniques for implant and explant are explained in detail.